Brand Storytelling on Websites: The Role of Empathy on Repurchase Intentions for PCs and Smartphones. Issue 1 (2nd January 2023) - Kato, Takumi
Abstract: While the model chosen for campaigns is crucial in gaining empathy, previous literature has primarily considered celebrities. Remarkably, literature includes no examples of unknown models focusing on empathy in product usage scenes. Therefore, the purpose of this study is to clarify the effect of empathy—or consumers' belief that the model uses products in the same way as in their daily lives—on repurchase intentions. As a result of applying a propensity score for personal computers and smartphones in Japan, the significant effect was shown. This result suggests that realistic depictions should be adopted in symbolizing product concepts.